Pemberdayaan Masyarakat dalam Implementasi Pembangunan Desa - Jaberan; Tampubolon, Frances Roi Seston (LANCAH: Jurnal Inovasi dan Tren, 2024)
Community empowerment in village development is very necessary, this can be used as a form of cooperation between the government and the community. Community empowerment can be carried out by many elements: government, universities, non-governmental organizations, the press, political parties, donor agencies, artists, civil society, or local community organizations themselves. This research method is a descriptive-qualitative research method, with data sources obtained from primary and secondary data. The data collection technique uses observation techniques. The results of the research obtained several solutions in empowering the community to implement village development, namely creating a climate, strengthening power, and protecting and the Rural Development Program.